2018
DOI: 10.1371/journal.pone.0200040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D on inflammatory and oxidative stress responses of human bronchial epithelial cells exposed to particulate matter

Abstract: BackgroundParticulate matter (PM) pollutant exposure, which induces oxidative stress and inflammation, and vitamin D insufficiency, which compromises immune regulation, are detrimental in asthma.ObjectivesMechanistic cell culture experiments were undertaken to ascertain whether vitamin D abrogates PM-induced inflammatory responses of human bronchial epithelial cells (HBECs) through enhancement of antioxidant pathways.MethodsTranscriptome analysis, PCR and ELISA were undertaken to delineate markers of inflammat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 72 publications
0
45
0
Order By: Relevance
“…As an antecedent at the respiratory level, vitamin D stimulated the activation of the glucose-6-phosphate dehydrogenase signaling pathway and the production of oxidized glutathione as antioxidant mechanisms against oxidative stress induced by pollutant particulate matter in human bronchial epithelial cells. Therefore, vitamin D may exert a protective antioxidant effect on lungs and airways under oxidative stress conditions such as asthma or chronic obstructive pulmonary disease in smoking patients [162,163]. In this regard, it was observed that patients with pulmonary pathologies usually have lowered vitamin D serum levels, which would indicate a possible correlation between an impaired antioxidant defense and a susceptibility to suffer lung disease [164].…”
Section: Vitamin D Antioxidative Actions Against Sars-cov-2 Infectionmentioning
confidence: 99%
“…As an antecedent at the respiratory level, vitamin D stimulated the activation of the glucose-6-phosphate dehydrogenase signaling pathway and the production of oxidized glutathione as antioxidant mechanisms against oxidative stress induced by pollutant particulate matter in human bronchial epithelial cells. Therefore, vitamin D may exert a protective antioxidant effect on lungs and airways under oxidative stress conditions such as asthma or chronic obstructive pulmonary disease in smoking patients [162,163]. In this regard, it was observed that patients with pulmonary pathologies usually have lowered vitamin D serum levels, which would indicate a possible correlation between an impaired antioxidant defense and a susceptibility to suffer lung disease [164].…”
Section: Vitamin D Antioxidative Actions Against Sars-cov-2 Infectionmentioning
confidence: 99%
“…In addition, it was suggested that S. pneumoniae produces hydrogen peroxide that damages the DNA and induces apoptosis in lung epithelial cells (Rai et al, 2015). Similarly, the toxicity of ASD is attributed to oxidative stress and apoptosis (Go et al, 2015;Chang et al, 2016;Pfeffer et al, 2018). Therefore, it appears that the additive effects of ASD and S. pneumoniae enhance apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative data suggest that vitamin D exerts anti-inflammatory effects via its actions on both innate and adaptive immune responses. Upon viral infection or exposure of pro-inflammatory stimuli such as Poly(I:C) or PM, 1,25(OH) 2 D attenuates induced expression of cytokines and chemokines e.g., via inhibition of nuclear factor (NF)-κB or oxidative stress, respectively, in (airway) epithelial cells (38,59,116). Furthermore, 1,25(OH) 2 D increases expression of the soluble decoy receptor for IL-33 (sST2) by airway epithelial cells, which in turn inhibits the actions of the type 2 alarmin IL-33 (117).…”
Section: Effects Of Vitamin D On Innate and Adaptive Immune Responsesmentioning
confidence: 99%